Non-Invasive Vagus Nerve Stimulation for the ACute Treatment of Cluster Headache: Findings From the Randomized, Double-Blind, Sham-Controlled ACT1 Study - Silberstein, Stephen D.; Mechtler, Laszlo L.; Kudrow, David B.; Calhoun, Anne H.; McClure, Candace; Saper, Joel R.; Liebler, Eric J.; Rubenstein Engel, Emily; Tepper, Stewart J. (Headache, 2016)
Objective To evaluate non‐invasive vagus nerve stimulation (nVNS) as an acute cluster headache (CH) treatment. Background Many patients with CH experience excruciating attacks at a frequency that is not sufficiently addressed by current symptomatic treatments. Methods One hundred fifty subjects were enrolled and randomized (1:1) to receive nVNS or sham treatment for ≤1 month during a double‐blind phase; completers could enter a 3‐month nVNS open‐label phase. The primary end point was response rate, defined as the proportion of subjects who achieved pain relief (pain intensity of 0 or 1) at 15 minutes after treatment initiation for the first CH attack without rescue medication use through 60 minutes. Secondary end points included the sustained response rate (15‐60 minutes). Subanalyses of episodic cluster headache (eCH) and chronic cluster headache (cCH) cohorts were prespecified. Results The intent‐to‐treat population comprised 133 subjects: 60 nVNS‐treated (eCH, n = 38; cCH, n = 22) and 73 sham‐treated (eCH, n = 47; cCH, n = 26). A response was achieved in 26.7% of nVNS‐treated subjects and 15.1% of sham‐treated subjects (P = .1). Response rates were significantly higher with nVNS than with sham for the eCH cohort (nVNS, 34.2%; sham, 10.6%; P = .008) but not the cCH cohort (nVNS, 13.6%; sham, 23.1%; P = .48). Sustained response rates were significantly higher with nVNS for the eCH cohort (P = .008) and total population (P = .04). Adverse device effects (ADEs) were reported by 35/150 (nVNS, 11; sham, 24) subjects in the double‐blind phase and 18/128 subjects in the open‐label phase. No serious ADEs occurred. Conclusions In one of the largest randomized sham‐controlled studies for acute CH treatment, the response rate was not significantly different (vs sham) for the total population; nVNS provided significant, clinically meaningful, rapid, and sustained benefits for eCH but not for cCH, which affected results in the total population. This safe and well‐tolerated treatment represents a novel and promising option for eCH. ClinicalTrials.gov identifier: NCT01792817.